Digital Budgeting Transformation and Future Challenges: A Bibliometric Analysis - Salahudin, Salahudin; Sihidi, Iradhad Taqwa; Karida, Kisman; Firdaus, Muhammad (Universitas Muhammadiyah Yogyakarta, 2024)
In the contemporary era, digital budgeting has become increasingly significant in enhancing operational efficiency, fostering transparency, and promoting stakeholder participation within budget management. This study endeavors to scrutinize prevailing research trends pertaining to digital budgeting by conducting a comprehensive analysis of publications indexed in the Scopus database. Utilizing bibliometric data analysis and Nvivo 12 Plus, our investigation facilitated the delineation of noteworthy findings. The study underscores a substantial surge in research interest surrounding digital budgeting, along with the noteworthy contributions from diverse countries to the research literature. The revealed insights affirm that digital budgeting transcends geographical boundaries, constituting a global phenomenon with diverse contextual applications and practices across the globe. Furthermore, the findings illuminated a broad spectrum of research topics related to digital budgeting, encompassing aspects such as the utilization of digital platforms, public participation, budget oversight, local-level budget management, and digital democracy. While acknowledging the immense potential of digital budgeting, it is imperative to recognize the challenges accompanying its implementation. These challenges encompass issues of data security, policy adaptation, organizational culture, constrained human resources, and system integration. This study advocates for a multidisciplinary approach as essential for mitigating the impediments and challenges inherent in the effective implementation of digital budgeting.